2011
DOI: 10.1068/p6825
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Hand: The Use of a Mirror Highlights the Contributions of Interpreted and Retinotopic Representations in the Rubber-Hand Illusion

Abstract: In the rubber-hand illusion, observing a rubber hand stroked in synchrony with one's own hand results in mislocalisation of the own hand, which is perceived as being located closer to the rubber hand. This illusion depends on having the rubber hand placed at a plausible egocentric orientation with respect to the observer. In the present study, we took advantage of this finding in order to compare the relative influence on the illusion of the rubber hand's perceived retinotopic image against its real-world posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…The rubber hand illusion (RHI) is an illusory experience of body ownership of a fake study supports this possibility; in it, the body ownership illusion was evoked 23 irrespective of the egocentric or allocentric fake hand images in a mirror [11]. The 24 present study pursues these hypothetical propositions.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…The rubber hand illusion (RHI) is an illusory experience of body ownership of a fake study supports this possibility; in it, the body ownership illusion was evoked 23 irrespective of the egocentric or allocentric fake hand images in a mirror [11]. The 24 present study pursues these hypothetical propositions.…”
Section: Introductionsupporting
confidence: 65%
“…29 Experiment 2 investigates whether the incongruency of the fake and actual hands' 30 postures (angles) is accepted in the RHI setting involving a mirror. Although Kontaris 31 and Downing [11] found that first-person and third-person perspective images of a fake 32 hand in a mirror did not differ in terms of the subjective experience of the 33 body-ownership illusion, they did not deal with situations where the actual and fake 34 hands were angled. Exp.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations